The potential of local Bacillus sp. BK7.1, EG6.4, and LSD4.2 as biocontrol agents against the pathogenic fungus Fusarium oxysporum - TRI NURHARIYATI; SALAMUN SALAMUN; AGUS SUPRIYANTO; TIMOTHY BAGASDO MATATIAS SINURAT; FIKA YULIANA; ALMANDO GERALDI; INTAN AYU PRATIWI; FARAH AISYAH NAFIDIASTRI; MAHDI IZZUDDIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Nurhariyati T, Salamun, Supriyanto A, Sinurat TBM, Yuliana F, Geraldi A, Pratiwi IA, Nafidiastri FA, Izzuddin M. 2025. The potential of local Bacillus sp. BK7.1, EG6.4, and LSD4.2 as biocontrol agents against the pathogenic fungus Fusarium oxysporum. Biodiversitas 26: 3273-3280. Plant-pathogenic fungi can cause horticultural wilt disease. Some Bacillus species exhibit antifungal activity against plant pathogens. This study aimed to examine the effects of several indigenous Bacillus species on the growth of Fusarium oxysporum. The research was conducted experimentally using a 5x6 factorial design. The first factor was isolate variation, consisting of Bacillus subtilis BK7.1, Bacillus mojavensis EG6.4, Bacillus velezensis LSD4.2, a negative control (C-), and a positive control (C+). The second factor was incubation time (contact time) at 1st, 2nd, 3rd, 4th, 5th, and 6th days.  This study tested the antifungal activity of Bacillus isolates and controls against F. oxysporum using the pour plate method. The growth of the pathogenic fungus was measured based on the diameter of the growth area of F. oxysporum. Antagonistic testing was conducted to determine whether the three isolates could be combined in a biofungicide consortium. Antifungal activity test results revealed that all isolates (BK7.1, EG6.4, and LSD4.2) effectively inhibited the growth rate of F. oxysporum. Variations in isolate type, incubation time, and combinations significantly affected the inhibition of F. oxysporum growth. The antagonistic activity test yielded negative results. Therefore, isolates BK7.1, EG6.4, and LSD4.2 will be developed as biofungicide candidates for the biocontrol of plant-pathogenic fungi.